Risk Factors for Presumed Bacterial Pneumonia Among HIV-uninfected Children Hospitalized in Soweto, South Africa. Issue 11 (November 2016) - Verani, Jennifer R.; Groome, Michelle J.; Zar, Heather J.; Zell, Elizabeth R.; Kapongo, Constant N.; Nzenze, Susan A.; Mulligan, Christine; Moore, David P.; Whitney, Cynthia G.; Madhi, Shabir A.
Abstract : Background: Pneumonia is a leading cause of child morbidity and death. Data on risk factors can guide prevention efforts. Within a study on pneumococcal conjugate vaccine effectiveness, we investigated risk factors for presumed bacterial pneumonia (PBP). Methods: PBP cases were human immunodeficiency virus (HIV) uninfected children with lower respiratory tract infection and consolidation on chest radiograph or nonconsolidated infiltrate with C-reactive protein ≥40 mg/L hospitalized at Chris Hani Baragwanath Academic Hospital (CHBAH) in Soweto. Age-matched community controls were identified using CHBAH birth records ±1 week of case birth date. Data were analyzed using conditional logistic regression. Results: A total of 889 PBP cases (median age 9 months) were matched to 2628 controls. Crowding was a significant risk factor among well-nourished children (adjusted odds ratio [aOR]: 2.29, 95% confidence interval [CI]: 1.89–2.78), but not in those with low weight-for-age. Malnutrition was associated with PBP; strength of association was highest in the absence of crowding (aOR: 6.68, 95% CI: 4.74–9.42). Exclusive breastfeeding was protective only among HIV-unexposed children (aOR: 0.65, 95% CI: 0.54–0.78). Self-reported maternal HIV infection was a risk factor among children exclusively breastfeed up to 4 months (aOR: 2.33, 95% CI: 1.53–3.55). Having indoor tap water was protective (aOR: 0.65, 95% CI: 0.54–0.78), whereas a primary care giver who smoked was a risk factor (aOR: 5.15, 95% CI: 2.94–9.03). Conclusions: Our findings confirm several known pneumonia risk factors and highlight complex interactions between factors, including HIV exposure, breastfeeding, malnutrition and crowding. Improved housing, reduced secondhand smoke exposure and HIV prevention among women of reproductive age could lessen the child pneumonia burden.